A Feasible Multimodal Photoacoustic Imaging Approach for Evaluating the Clinical Symptoms of Inflammatory Arthritis. (21st August 2022) - Rajasekar, B.; Nirmala, P.; Bhuvaneswari, P.; Radhika, R.; Asha, S.; Kavitha, K. R.; Belay, Semagn Shifere
Abstract : Numerous traditional medical imaging methods, including computed tomography with X-rays, positron emission tomography (PET), and magnetic resonance imaging (MRI), are utilized frequently in medical settings to screen for illnesses, diagnose patients, and track the effectiveness of treatments. When examining bone protrusions, CT is preferred over MRI for scanning connective tissue. Although the picture quality of PET is inferior to that of CT and MR, it is outstanding for detecting the molecular markers and metabolic functions of illnesses. To give high-resolution structural pictures and improved ailment sensitivity and specificity within another image, multimodal data and substantial therapeutic influence on advanced diagnostics and therapeutics have been used. The goal was to evaluate the clinical significance of multimodal photoacoustic/ultrasound (PA/US) articular imaging scoring, a cutting-edge image technique that may show the microvessels and oxygen levels of rheumatoid arthritis-related inflamed joints (RA). The PA/US imaging technology analyzed seven tiny joints. The PA and power Doppler (PD) impulses were semiquantified using a 0–3 grading scale, and the averages of the PA and PD scores for the seven joints are computed. Three PA+SO2 types were found determined by the relative oxygen levels (SO2 ) measurements of the affected joints. Researchers evaluated the relationships between the disease activity ratings and the PA/US imaging ratings. The PA scores and medical ratings that reflect the extent of the pain have strong relationships with each other, as do the PA+SO2 combinations. PA may be clinically useful in assessing RA. Thus, the research evaluated the clinical symptoms of inflammatory arthritis using a multimodal photoacoustic image process.